Blending Influence on the Conversion Efficiency of the Cogasification Process of Corn Stover and Coal - Anthony Ike Anukam; Sampson Ntshengedzeni Mamphweli; Polycarp Sbusiso Mabizela; Edson Leroy Meyer (Journal of Chemistry)
Characterizations of biomass and coal were undertaken in order to compare their properties and determine the combustion characteristics of both feedstocks. The study was also intended to establish whether the biomass (corn stover) used for this study is a suitable feedstock for blending with coal for the purpose of cogasification based on composition and properties. Proximate and ultimate analyses as well as energy value of both samples including their blends were undertaken and results showed that corn stover is a biomass material well suited for blending with coal for the purpose of cogasification, given its high volatile matter content which was measured and found to be 75.3% and its low ash content of 3.3% including its moderate calorific value of 16.1%. The results of the compositional analyses of both pure and blended samples of corn stover and coal were used to conduct computer simulation of the cogasification processes in order to establish the best blend that would result in optimum cogasification efficiency under standard gasifier operating conditions. The final result of the cogasification simulation process indicated that 90% corn stover/10% coal resulted in a maximum efficiency of about 58% because conversion was efficiently achieved at a temperature that is intermediate to that of coal and corn stover independently.